Instalación, Verificación de la Calibración y Aplicación del Ensayo Triaxial del CIVCO utilizando diferentes tipos de Suelo - Dotti-Sanabria, Ruy Eduardo (Instituto Tecnológico de Costa Rica, 2008)
The main goal of this project is to coordinate the installation, check the calibration, and utilize the triaxial apparatus from CIVCO. The triaxial test is the most sophisticated of the soil shear strength tests. This test consists of reproducing the confinement in which a section of soil in situ. A specimen of soil in the shape of a cylinder is placed inside a sealed chamber. Then, under an uniformed pressure, a load is applied by means of a piston and a load frame until the specimen fails. Three types of specimens were taken from Cartago and San José proper characterization and classification. Type triaxial testing UU and CU was performed an automatic equipment for data acquisition. The results were use to design a mat foundation for each studied soil. The CIVCO triaxial machine is one of the very few ones existing in Costa Rica; therefore, it is of great importance its habilitation.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2008.
Keywords: Resistencia; Cohesión; Fricción; Drenaje; Transductor